A case report on right ovarian molar ectopic pregnancy - Mashruwala, Vishrut M.; Patel, Amrita D.; Kumari, Maya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Ectopic gestation has an incidence rate of 4.5-16.8/1000 pregnancies. Hydatidiform moles can be complete or incomplete and incidence is around 1-3/1000 pregnancies. Tubal ectopic hydatidiform moles are quiet rare lesions, and 132 cases have been reported in the world literature; 1.5/10,00,000 pregnancies. The present case conveys the importance of histological examination of products of conception which helps to provide an appropriate diagnosis, thereby the clinician can offer appropriate counselling and follow up to the patient.